2015
DOI: 10.1016/j.metabol.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of the Vitamin D Metabolite 1,25(OH)2D and Odds of Metabolic Syndrome and its Components

Abstract: Aim Few epidemiological studies have investigated the association between circulating concentrations of the active vitamin D metabolite 1,25(OH)2D and metabolic syndrome. We sought to determine whether blood levels of 1,25(OH)2D are associated with metabolic syndrome and its individual components, including waist circumference, triglycerides, blood pressure, and glucose, and high-density lipoprotein. We also investigated these associations for the more abundant precursor vitamin D metabolite, 25(OH)D. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 45 publications
5
41
0
3
Order By: Relevance
“…Addition to its classical roles in promoting calcium and phosphorus adsorption, vitamin D in its active format as calcitriol functions like sterol hormones to regulate diverse biological functions from the host immune response to cell differentiation (Adams and Hewison, 2010). Although, high calorie diet including high fat diet (HFD) is thought to be a major cause of IR, NAFLD, and MetS, the epidemiologic evidence also shows an association of VDD in development of MetS (Botella-Carretero et al, 2007; Lu et al, 2009; Barchetta et al, 2011; Bea et al, 2015). In animal experiments, dietary vitamin D deficiency was found to exacerbate Toll-like receptor activation and hepatic inflammation in obese rats (Roth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Addition to its classical roles in promoting calcium and phosphorus adsorption, vitamin D in its active format as calcitriol functions like sterol hormones to regulate diverse biological functions from the host immune response to cell differentiation (Adams and Hewison, 2010). Although, high calorie diet including high fat diet (HFD) is thought to be a major cause of IR, NAFLD, and MetS, the epidemiologic evidence also shows an association of VDD in development of MetS (Botella-Carretero et al, 2007; Lu et al, 2009; Barchetta et al, 2011; Bea et al, 2015). In animal experiments, dietary vitamin D deficiency was found to exacerbate Toll-like receptor activation and hepatic inflammation in obese rats (Roth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This hormonally active metabolite can directly stimulate expression of the insulin receptor [11] and/or have indirect insulin-sensitizing effects through regulation of extracellular calcium [9]. While production of 1,25(OH) 2 D is tightly regulated to maintain calcium balance [12], more recently, it was suggested that 1,25(OH) 2 D has independent effects on features of the metabolic syndrome [13]. Clinical data, however, have been scarce and inconsistent: some studies reported an association between reduced 25(OH)D and insulin resistance in various populations [2,5,8], whereas others reported no such associations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study within the UDCA cohort included in the present study, moderate to vigorous physical activity was positively associated with 1,25 (OH) 2 D, with women experiencing the greatest increase (21). Hibler et al (21) suggested that the association between physical activity and vitamin D may be beyond sun exposure and driven (63). The major strengths of the current study include the availability of data from a prospective cohort of >1300 participants with complete data on a wide range of available baseline nutrition, physical activity, and serum vitamin D metabolite data.…”
Section: Discussionmentioning
confidence: 97%